The Children's book of Islam. Part two - Ahsan, M. M (Leicester, England : Islamic Foundation, 1993)
Foundamental passages and tenants of Islam for beginners, followed by a "workbook" of questions
Ibadah (Worship in Islam)
1
Keywords: Islam; Islamic religious education of children